Olimpiodoro sobre la retórica en el Gorgias: un ejemplo de filosofía como armonización - Jiménez, Marta (Pontificia Universidad Católica del Perú, 2025)
The aim of this paper is to study the interpretative strategies employed by Olympiodorus in his Commentary on Plato’s Gorgias, and defend the thesis that it is an example of a refined and complex philosophical hermeneutics. Rather than merely reproducing without critique Socrates’ proposal concerning rhetoric or distorting it to serve his own interests, Olympiodorus presents a philosophically sophisticated interpretation of the Socratic premises in light of the distinctions made by Socrates himself in the dialogue. Thus, he shows how Plato’s position is more coherent with his own stance than the theories of the Aristotelians and the Stoics. Although Olympiodorus seeks to show that there exists a form of oratory that can be considered a legitimate practice, his proposal does not amount to a mere biased defense of oratory, but rather constitutes an attempt to philosophically solve the tensions that arise from the Gorgias. He uses a dual strategy: on the one hand, he disentangles the concept of experience (empeiria) from the concept of adulation (kolakeia), and on the other hand, he acknowledges experiential practices as legitimate arts and forms of knowledge. This enables him to differentiate between various ways of practicing rhetoric and to create a space for rhetoric as a legitimate practice with a political and ethical purpose. Olympiodorus uses sophisticated philosophical methods to uncover harmony beneath the apparent disagreement and thus creates a space for the practice of rhetoric as a respected profession.

El objetivo de este trabajo es estudiar las estrategias interpretativas de Olimpiodoro en su comentario al Gorgias, y defender que es un ejemplo de hermenéutica filosófica refinada y compleja. Lejos de simplemente reproducir sin crítica la propuesta de Sócrates sobre la retórica o de deformarla para encajar en sus intereses, Olimpiodoro propone una interpretación filosóficamente sofisticada de las premisas Socráticas a la luz de distinciones que el mismo Sócrates hace en el diálogo. El comentario de Olimpiodoro muestra, así, cómo la posición de Platón es más coherente con su propio criterio y con teorías Aristotélicas y Estoicas. Aunque el objetivo de Olimpiodoro sea mostrar que existe una oratoria que es una práctica legítima, su propuesta no es una mera defensa interesada de la oratoria, sino un intento de resolver filosóficamente las tensiones que surgen en el Gorgias. Su estrategia es doble: desenmarañar el concepto de experiencia (empeiria) del de adulación (kolakeia) y abrir espacio a las prácticas experienciales como artes o saberes legítimos, lo que le permite distinguir varias formas de practicar la retórica y encontrar lugar para la retórica como práctica legítima con utilidad política y ética. Olimpiodoro utiliza métodos filosóficos sofisticados para encontrar armonía bajo el aparente desacuerdo y así abrir espacio para la práctica de la retórica como una profesión respetable.
Keywords: Olympiodorus; Rhetoric; Method; Interpretation; Harmonization; Olimpiodoro; Retórica; Método; Interpretación; Armonización; https://purl.org/pe-repo/ocde/ford#6.03.01